Place identity in a personality psychological context: place identity orientation and its validating associations with nature connectedness and pro-environmental behavior - Berze, Iván Zsolt; Dúll, Andrea (Frontiers in Psychology, 2024)
In the frame of the inner–outer (personal–social) dichotomy in theories of social or personality psychology, it is argued in this study that, as a new approach, it is reasonable to examine individual differences in tending to orient toward another outer facet, not just social, i.e., the surrounding socio-physical environment while defining the self-concept—first performing it at the level of place-scaled meaningful settings, thus, interpreting place identity in the context of identity orientations. The present research aimed to theoretically and methodologically support a new concept based on this approach: place identity orientation (PIO). For the latter purpose, the development process of the questionnaire measuring it, which was based on supplementing the Aspects of Identity Questionnaire (AIQ-IV), was completed. In addition, the new construct was validated based on the relationships discussed in literature between place identity, connectedness with a larger-scaled environment, i.e., nature, and pro-environmental behavior (PEB), moreover, identity orientations and behavior. In our first scanning step of validating PIO, a partial mediation between PIO and PEB through nature connectedness was found among 1,281 adults. It suggests that the relative importance of the relationship with places in self-definition has a distinct role in addition to nature connectedness in behaving pro-environmentally. Limitations and future research directions (e.g., using PIO to examine people–environment fit in several settings) are also discussed.